A Comparative Analysis of Elementary School Students' Attitudes Toward Science Practicum Activities - Yuhaniz Aqila; Hisny Fajrussalam; Nenden Permas Hikmatunisa; Mariano Dos Santos (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
Science practicum activities are an important component of science learning because they help students understand concepts through direct experience. This study aimed to conduct a comparative analysis of third-grade and fifth-grade elementary school students' attitudes toward science practicum activities, identify students' positive attitudes toward practicum activities, and examine the consistency of elementary school students' scientific attitudes. The study employed a descriptive qualitative approach involving 180 elementary school students, consisting of 90 third-grade students and 90 fifth-grade students. Data were collected through questionnaires on students' attitudes toward science practicum activities and scientific attitudes, and were analyzed descriptively using percentages. The findings revealed differences in attitudes toward science practicum activities between third-grade and fifth-grade students, with fifth-grade students demonstrating more positive attitudes than third-grade students. In general, elementary school students showed positive responses to science practicum activities because these activities provided engaging, enjoyable, and meaningful learning experiences that facilitated direct understanding of scientific concepts. However, fifth-grade students exhibited higher levels of interest, participation, and enthusiasm than third-grade students. The results also indicated that fifth-grade students demonstrated greater consistency in scientific attitudes during practicum activities. Science practicum activities contribute to the development of students' curiosity, cooperation, honesty, and thinking skills. Therefore, science practicum activities play an important role in supporting the development of students' attitudes and enhancing the quality of science learning in elementary schools